Now/Here/Nowhere - Panayides, Angelos (My University, 2025)
I am honored to serve as a member of the International Jury for the 7th Emirates International Poster Festival (EIPF) 2025, taking place in Dubai from November 3 to December 31, 2025, in celebration of the UAE’s Year of Community 2025. In this spirit of connection and inclusion, I am pleased to personally invite you to participate in this year’s festival — a leading platform for poster design & visual communication in the MENA region that celebrates design as a bridge between cultures, disciplines, and communities. Your work has consistently inspired dialogue and reflection, and I be- lieve your voice would make a meaningful contribution to this year’s theme: “Design Connects: Bridging Cultures, Building Communities”. We welcome creative interpretations of: • Cross-cultural exchange • Identity and belonging • Social inclusion and diversity • Collaborative storytelling • Design as a tool for unity and understanding Why Submit? • Your work will be considered for exhibition in Dubai and featured in the digital exhibition catalogue. • All selected participants receive a Certificate of Participation. • This is a unique opportunity to engage in a global design dialogue and connect with artists and educators from around the world. Key Details: • Format: 70 x 100 cm, vertical, JPEG, RGB, 300 dpi • Filename: Name_Surname_Country_Postertitle.jpeg • Submission Link: https://forms.gle/3yUT5tV42eP8EYW28 • Deadline: September 20, 2025 • Announcement of Selected Works: September 30, 2025 As a designer invited by a jury member, your submission will skip the pre-selection process and advance directly to the final evaluation by the international jury. I would be honored to see your interpretation of this year’s theme and to welcome your work into the 7th EIPF.
Design Connects: Bridging Cultures, Building Communities. Identity and belonging
Keywords: International, Graphic Design, Poster, Festival, Exhibition